2021
DOI: 10.1177/00034894211024051
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of 3D Models for Microtia Reconstruction Using Smartphone-Based Technology

Abstract: Objective: Microtia reconstruction is technically challenging due to the intricate contours of the ear. It is common practice to use a two-dimensional tracing of the patient’s normal ear as a template for the reconstruction of the affected side. Recent advances in three-dimensional (3D) surface scanning and printing have expanded the ability to create surgical models preoperatively. This study aims to describe a simple and affordable process to fabricate patient-specific 3D ear models for use in the operating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The use of 3D-printed templates also led to higher precision rates with lower mean errors for auricular length (0.39 ± 0.35 vs. 1.80 ± 1.44 mm; P <0.001) and width (0.30 ± 0.47 vs. 1.32 ± 0.88 mm; P <0.001) compared to X-ray films 6 , 27 . Furthermore, three technical notes and a case series demonstrated that the surgeons had noticed that using a 3D guide provided better accuracy 5 , 24 , 26 . The quality of the included cohort studies indicated a medium to low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…The use of 3D-printed templates also led to higher precision rates with lower mean errors for auricular length (0.39 ± 0.35 vs. 1.80 ± 1.44 mm; P <0.001) and width (0.30 ± 0.47 vs. 1.32 ± 0.88 mm; P <0.001) compared to X-ray films 6 , 27 . Furthermore, three technical notes and a case series demonstrated that the surgeons had noticed that using a 3D guide provided better accuracy 5 , 24 , 26 . The quality of the included cohort studies indicated a medium to low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Jeon et al 18 proposed a mirrored, sterilizable 3D print of the ear that can be used as a guide during reconstructive surgery. You et al 30 proposed a simplification of this approach by using a lidar iPhone camera instead of expensive 3D scanners to simplify and reduce the costs of this kind of surgery. Alhazmi et al 31 introduced a prefabricated, standard template that is sterilizable and printable in many sizes.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study comparing various systems found that cheaper and more accessible systems (such as the iPhone) showed impressive results, considering it as an alternative to more expensive systems [16]. There have been subsequent publications that confirm the exactness and reliability of the systems, with similar acquisition times, making these systems more accessible and convenient for everyday practice [17].…”
Section: Discussionmentioning
confidence: 99%